Implementation Of Financial Management Of Simpang Sari Village, Sumber Jaya District, West Lampung Regency - Satirmanudin, Sukrul; Corry Wardhani, Andy; Susanto , Agus (Jurnal Info Sains : Informatika dan Sains, 2024)
The village government is required to prepare a report on the realisation of the implementation of the Village Revenue and Expenditure Budget (APB) and the Accountability Report. The preparation of financial reports carried out by Simpang Sari village officials. In the preparation of financial reports carried out by Simpang Sari village officials, there are differences in the data presented, financial information is not transparent and difficult to understand by the public, so that village financial reports become less accurate or cannot be presented properly, the presentation of village financial reports is often not in accordance with correct accounting principles so that it is difficult to understand budget fluctuations and finally weak supervision. This study aims to determine the implementation of financial management of the Simpang Sari village fund, Sumberjaya District, West Lampung Regency. This research is a descriptive qualitative research with a policy implementation theory approach, which was conducted in Simpang Sari Village, West Lampung District. The results of the study can be concluded that the implementation of financial management of Simpang Sari Village, Sumber Jaya Subdistrict, West Lampung Regency can be explained by the village apparatus has carried out financial management procedures with accountability and transparency referring to Permendagri Number 20 of 2018. The financial management has also been realised in the form of public policy programs.